2009
DOI: 10.1021/jp906040a
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Oscillations, Complex Oscillations, and Elimination of Extraordinary Temperature Sensitivity in the Iodate−Sulfite−Thiosulfate Flow System

Abstract: Temperature oscillations and complex pH oscillations in the IO(3)(-)-SO(3)(2-)-S(2)O(3)(2-) system were observed in a continuously flow stirred tank reactor. During one period of oscillation, the temperature increases rapidly while the pH shows an extremely sharp change. High-amplitude pH oscillations undergo 1(1) complex oscillations (L(S), oscillations with L large peaks and S small peaks per period) to another kind of higher-amplitude regular oscillations upon increasing the concentration of sulfite step by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…3.1 Extention of the IST model for complex oscillations of the TuIS system 3.1.1 Model. In our previous paper 5 we have successfully demonstrated that a simple empirical rate law model suggested by Horva´th 20 can easily explain the experimentally observed complex oscillations in the IST system. The four-step model consisted of a protonation equilibrium between sulfite and hydrogensulfite, the Landolt reaction (sulfite-iodate reaction) and the complex thiosulfate-iodate reaction leading to the formation of tetrathionate or hydrogensulfite simultaneously.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…3.1 Extention of the IST model for complex oscillations of the TuIS system 3.1.1 Model. In our previous paper 5 we have successfully demonstrated that a simple empirical rate law model suggested by Horva´th 20 can easily explain the experimentally observed complex oscillations in the IST system. The four-step model consisted of a protonation equilibrium between sulfite and hydrogensulfite, the Landolt reaction (sulfite-iodate reaction) and the complex thiosulfate-iodate reaction leading to the formation of tetrathionate or hydrogensulfite simultaneously.…”
Section: Resultsmentioning
confidence: 94%
“…4 Recently, complex pH oscillations were reported in the iodate-sulfite-thiosulfate (IST) system. 5 Since pattern formation in chemical reaction-diffusion systems is a paradigm for self-organization phenomena far from thermodynamic equilibrium, 6 the studies of patterns have been a stimulating and challenging project in sulfur-based systems excluding the classical BZ [7][8][9] and chlorite-iodide-malonic acid (CIMA) 10 reactions. A large variety of spatial patterns 11,12 such as self-replicating spots, bouncing waves, and stationary labyrinthine patterns were found in the ferrocyanide-iodatesulfite (FIS) reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Through the vessel’s acrylic lid three 18 G needles connected to micro-bore tubing to feed reactants to the bottom of the vessel. Solution B and D (sulphite and sulfuric acid) were mixed just prior to injection in order to limit local acidification 39 , while C and E were also premixed in this fashion. Nitrogen was continuously fed to the reactor to reduce atmospheric contamination.…”
Section: Methodsmentioning
confidence: 99%
“…Feed streams (3) and (4) were premixed in a premixing head, just before their entry into the reactor, which effectively avoided local acidification. 29…”
Section: Experimental Section 1 Cstr Experimentsmentioning
confidence: 99%
“…For an analogous Landolt-type reaction, the iodate-sulfite-thiosulfate (IST) reaction, which is autocatalytic with respect to both protons and iodide ions, shows complex pH oscillations and temperature oscillations in a continuous flow stirred tank reactor (CSTR) [27][28][29] and produces pH waves and iodine waves in a Petri dish. 30 In this paper, we focus on the pH and triiodidestarch complex pattern formation obtained by using sodiumpolyacrylate as the hydrogen ion binding agent, bromocresol green as the pH indicator, and starch as the simultaneous binding agent and indicator, respectively.…”
Section: Introductionmentioning
confidence: 99%